Blockchain Solutions for the Business World - Marek SZTURO; Karolina SZTURO (Communications of International Proceedings, 2025)
Blockchain technology, based on a decentralized ledger, is finding increasingly broad applications across various sectors of the economy. Its features, such as transparency, immutability of records, and the ability to automate processes through smart contracts, create new opportunities for the development of business models. This article presents the main directions of blockchain adoption in economic activity, including the financial sector, logistics, supply chain management, as well as data protection and digital identity. The analysis addresses the potential benefits of implementing this technology, as well as the barriers to its adoption, including regulatory, technical, and organizational challenges. The aim of the study is to highlight the opportunities that blockchain brings for innovation and the transformation of modern business.
Keywords: blockchain technology; smart contracts; digital economy.